(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Background: Physical activity (PA) is vital for maintaining health, mobility, and wellbeing in later life. However, many older adults in Saudi Arabia encounter barriers that prevent them from remaining active. These obstacles are often deeply ingrained in cultural values, gender expectations, family roles, and environmental factors like climate. To comprehend what facilitates or obstructs older adults from participating in PA, it is essential to listen not only to them but also to their caregivers. Including caregivers provides additional insight into barriers and facilitators, as they directly influence older adults’ ability to engage in physical activities. Aim: To explore cultural factors influencing PA adherence among older adults from the perspective of older adults and their caregivers. Methods: Semi-structured interviews were carried out with 15 older adults and their 15 family caregivers (15 dyads) in Northern Saudi Arabia. Dyads explored daily routines, beliefs about ageing and activity, and the role of family and culture in PA. Results: The early findings reveal that cultural expectations surrounding age, gender, and family roles significantly influence the perception and practice of PA. When PA occurred, it typically served a functional purpose, such as walking to the mosque or moving around the home, rather than for leisure. A recurring theme was the notion of balance; both older adults and caregivers continually evaluated the benefits of remaining active against the risks of fatigue, illness, or social disapproval. Many older adults expressed a preference for a quiet, restful life centred on family, while caregivers were often faced with trying to weigh up the benefits of PA with concern for their loved one, uncertain about how much activity was safe or suitable. Conclusion: This study provides insight into how cultural and relational dynamics influence PA in later life. The findings indicate that efforts to promote active ageing in this context must be culturally sensitive, family-oriented, and realistic about the physical and social environments in which older people reside. Keywords: Physical activity, DM, CKD, older adults, culture